“We Believe the Bible”: Cambodian Women in Christian Leadership, 1953–Present - Briana Wong (Indonesian Journal of Theology, 2021)
Christianity is a small but growing minority in Cambodia, accounting for only about 3% of the population yet growing there at a rate faster than in any other country in Southeast Asia. In Cambodian Christian communities, it is not uncommon to find more women than men in the churches. Cambodian boys often spend a brief period of their youth as novice monks at Theravada Buddhist monasteries, during which time they have the opportunity to become familiar with the Pali language and holy texts. Girls are not afforded this same opportunity, as there are no nuns (bhikkhuni) in contemporary Theravada. Within the Christian community in Cambodia, women carry out much of the service work in the churches, but only rarely are they invited to preach, let alone to become pastors—as is the case in much of the world. This article, based on interviews and participant observation with evangelical churches in Cambodia in 2019, demonstrates the ways in which ministry carried out by women has been characterized by courageous creativity, empowered through physical distance, and undergirded by a resoluteness of vocation.